Characterization of Lignin Isolated from Iranian Carpinus betulus Wood - Afshari, Hossein; Sheikh Bostanabad, Ali; Sadeghifar, Hassan; Ali Khalilzadeh, Ahmad; Ghaffar Ebadi, Abdol (Asian Journal of Chemistry, 2011)
Lignin isolated from Carpinus betulus by acidolytic dioxane method were characterized using alkaline nitrobenzene oxidation, elemental analysis, molecular weight analysis, GC-MS or gas chromatography-mass spectrometry, FT-IR and 1H NMR spectroscopy. The results showed that Mw (weight average molecular weight) and Mn (number average molecular weight) of the lignin is 8377.3 g/mol and 5152.8 g/mol, respectively. The ratio of S unit to G unit is 3.88 and C9 formula of Carpinus betulus lignin is C9 Hal2.296Hph 1.751O2.104(OH)ph 0.477(OH)al 1.409(OCH3)1.76.